Integration of family planning with maternal health services: an opportunity to increase postpartum modern contraceptive use in urban Uttar Pradesh, India. Issue 2 (30th November 2015) - Achyut, Pranita; Mishra, Anurag; Montana, Livia; Sengupta, Ranajit; Calhoun, Lisa M; Nanda, Priya
Abstract : Background: Maternal health (MH) services provide an invaluable opportunity to inform and educate women about family planning (FP). It is expected that this would enable women to choose an appropriate method and initiate contraception early in the postpartum period. In this study we examined interactions with health providers for MH services, and the effect of FP information provision during these interactions on the postpartum use of modern contraceptive methods. Methods: This study used midline data collected from 990 women who had delivered a live birth between January 2010 and the date of the midline survey in 2012. These women were asked a series of questions about their last delivery, including interactions with health providers during pregnancy, delivery and the postpartum period, if they received FP information during these interactions, and their contraceptive use during the postpartum period. Results: The study found that FP information provision as part of antenatal care in the third trimester, delivery and the postpartum period have a positive association with postpartum modern contraceptive use in urban Uttar Pradesh. However, health providers often miss these opportunities. Despite a high proportion of women coming into contact with health providers when utilising MH services, only a small proportion received FP information during these interactions. Conclusions: Integration of FP with MH services can increase postpartum modern contraceptive use. With the launch of the National Urban Health Mission, there now exists appropriate policy and programmatic environments for integration of FP and MH services in urban settings in India. However, this will require a concentrated effort both to enhance the capacity of health providers and encourage supportive supervision.